2016
DOI: 10.1021/acs.jctc.6b00937
|View full text |Cite
|
Sign up to set email alerts
|

Where Does the Density Localize? Convergent Behavior for Global Hybrids, Range Separation, and DFT+U

Abstract: Approximate density functional theory (DFT) suffers from many-electron selfinteraction error, otherwise known as delocalization error, that may be diagnosed and then corrected through elimination of the deviation from exact piecewise linear behavior between integer electron numbers. Although paths to correction of energetic delocalization error are wellestablished, the impact of these corrections on the electron density is less well-studied. Here, we compare the effect on density delocalization of DFT+U, globa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(127 citation statements)
references
References 133 publications
9
117
0
Order By: Relevance
“…Examining shapes and parameters of fit expressions across elements confirms that errors are generally the same shape but this also leads to observations consistent with earlier work on only delocalization error 38,44,[57][58][59][60] : heavier elements exhibit reduced convexity and concavity as the addition or removal of a single electron becomes a smaller fraction of total electron count (i.e., smaller coefficients in fits, Supporting Information Tables S3-S14).…”
supporting
confidence: 85%
“…Examining shapes and parameters of fit expressions across elements confirms that errors are generally the same shape but this also leads to observations consistent with earlier work on only delocalization error 38,44,[57][58][59][60] : heavier elements exhibit reduced convexity and concavity as the addition or removal of a single electron becomes a smaller fraction of total electron count (i.e., smaller coefficients in fits, Supporting Information Tables S3-S14).…”
supporting
confidence: 85%
“…[41][42][43] However, disadvantages for DFT+U remain in the fact that one must calculate [43][44] or tune the U parameter, which introduces empiricism. We have also shown that optimal U choice may be ambiguous, depending on whether one is aiming to reproduce accurate density properties 14 , recover piecewise linearity 45 , or reproduce spin-state ordering [41][42][43] .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the notion that higher-level methods, such as hybrid functionals, or the use of "DFT+U" or "DFT+Anderson impurity" methods [90,[101][102][103], are necessary to properly capture magnetic properties of molecular systems [58][59][60][61][62]104,105]; note that the latter two methodologies are also known to have their own intrinsic limitations for describing theoretically the properties of these systems [90,106]. Precedent for this statement can be found for the case of gas-phase transition-metal complexes, where it has been shown that with increasing amount of exact exchange, the ground-state charge density within the complexes localizes more in the ligand region than on the metal and the splitting between low-and high-spin states increases [107]. Indeed, due to the inclusion of exact exchange, hybrid functionals are able to better describe exchange-coupling effects between spin-parallel electrons, which are not fully captured by semilocal DFT functionals such as PBE [57][58][59][60][61]63].…”
Section: E Impact Of the Dft Functionalmentioning
confidence: 99%